Cloning, sequencing, expression and characterization of DNA photolyase from Salmonella typhimurium. - Li, Y F (1991)
We have cloned the phr gene that encodes DNA photolyase from Salmonella typhimurium by in vivo complementation of Escherichia coli phr gene defect. The S.typhimurium phr gene is 1419 base pairs long and the deduced amino acid sequence has 80% identity with that of E. coli photolyase. We expressed the S.typhimurium phr gene in E.coli by ligating the E.coli trc promoter 5' to the gene, and purified the enzyme to near homogeneity. The apparent molecular weight of S.typhimurium photolyase is 54,000 dalton as determined by SDS-polyacrylamide gel electrophoresis, which is consistent with the calculated molecular weight of 53,932 dalton from the deduced phr gene product. S.typhimurium photolyase is purple-blue in color with near UV-visible absorption peaks at 384, 480, 580, and 625 nm and a fluorescence peak at 470 nm. From the characteristic absorption and fluorescence spectra and reconstitution experiments, S.typhimurium photolyase appears to contain flavin and methenyltetrahydrofolate as chromophore-cofactors as do the E.coli and yeast photolyases. Thus, S.typhimurium protein is the third folate class photolyase to be cloned and characterized to date. The binding constant of S.typhimurium photolyase to thymine dimer in DNA is kD = 1.6 x 10(-9) M, and the quantum yield of photorepair at 384 nm is 0.5.